The deliverance of others - Palumbo-Liu, David (Duke University Press, 2012)
When otherness overcomes reason – Whose story is it? – Art: a foreign exchange – Pacific Ocean feeling: affect, otherness, mediation
10.1215/9780822395485
Keywords: Literature and globalization; Other (Philosophy) in literature; Intercultural communication in literature; Electronic books; lcgft; Englisch; Das Andere; Globalisierung; Literatur; Kulturkontakt; Verschiedenheit